SOSIALISASI OLAHRAGA PETANQUE KEPADA REMAJA DI DESA PASIR GALA GABUNGAN KECAMATAN LAWE BULAN KABUPATEN ACEH TENGGARA - Orbit Irwansyah; Muhammad Yassir; Muridha Hasan; Muhammad Tahir; Makmur Hartono; Ladipin; Habibul Akram (CV. Armas Suan Sejahtera, 2024)
The main problem faced by partners is that the teenagers of Pasir Gala Selamat Village, Lawe Bulan District, Southeast Aceh Regency, are not yet familiar with the game of petanque. Therefore, it is necessary to introduce the sport of petanque to the youth of Pasir Gala Selamat Village, Lawe Bulan District, Southeast Aceh Regency through integrated outreach. Participants in this training activity were 25 teenage participants, both boys and girls aged 10-14 years. Socialization activities will be held on 21-24 May 2024, 15.00 – 16.35 WIB. The stages in this activity are discussions with youth organizations and village officials, introduction to petanque games, practice and mentoring, petanque competitions and evaluation. The methods used are lectures, demonstrations, discussions and evaluations. Based on the results of the analysis of this activity, it can be concluded that the socialization was well received and could be a means for teenagers in the village of Pasir Gala Selamat, Lawe Bulan District, Southeast Aceh Regency to start practicing petanque.